Adverbials and inversion in early english scientific writing - Romero-Barranco, Jesús (My University, 2015)
From a historical perspective, the English language shifted from being basically verb final in the Old English period (Traugott 1992: 274) to verb non-final from the Middle English period onwards (Fischer 1992: 371), that is, from SOV to SVO. The layout of the constituents within the clause, however, may be occasionally inverted (from SV to VS) in certain contexts, which "have been qualified as innovations by some scholars and as true verb-second fossils by others" (Nevalainen 1997: 203). From a diachronic point of view, while inversion in Old English is possible whenever the first constituent position is occupied by an object, an adverbial or a PP, inversion in Middle English is just witnessed when the first constituent is a wh-element or, later on, a negative constituent (van Kemenade 1987: 180). Interestingly enough, research on the topic have demonstrated that instances of inversion after adverbials in first constituent position have been found in the early Modern English period, where the remainders of the old verb-second rule can be attested (Nevalainen 1997: 213; Bækken 2000: 393). In my opinion, there is still a gap in the literature since the phenomenon has not been tested in scientific writing yet. All this considered, the present paper has been conceived with the following objectives: 1) to analyse the occurrence of inversion when adverbials (then, therefore, yet, thus and locative PPs) or negative constituents (ne, never, neither and nor) occupy the first constituent position both in main and subordinate clauses; 2) to plot the diachronic development of inversion in the period under study; 3) to investigate the proliferation of the phenomenon across the different text-types; and 4) to evaluate the contribution of conditioning factors such as the typology of the subject or the typology of the clause. The data used as source of evidence come from The Corpus of Early English Medical Writing, i.e. Middle English Medical Texts (MEMT for the period 1375–1500) and Early Modern English Medical Texts (EMEMT for the period 1500–1700).
Keywords: Lingüística - Congresos; Linguistics; Syntax; Inversion; Fronted adverbials